Effects of change position in bed on vascular complications after coronary angiography - Ashketorab, T; Neishabory, N; Ghezelghash, A; Piranfar, A; Alavi- Majd, H (Advances in Nursing & Midwifery, 2009)
Abstract Introduction: Angiography is the most common invasive method for assessing coronary artery disease. This method is associated with vascular complications such as bleeding, hematoma and arterial thrombosis. To prevent these complications, patients are restricted to bed in supine position after the procedure, which is associated with back pain and discomfort. change Position in bed is considered an alteration in routine care protocols after coronary angiography, improving patients’ comfort and satisfaction. Purpose: This clinical trial was conducted to identify the effects of position change in bed on vascular complications after coronary angiography. Materials and Methods: 130 patients hospitalized for coronary angiography were enrolled in the study and randomly divided into two equal control and experimental groups. The control group remained supine in bed during the first 6 hours after coronary angiography. The position of patients in the experimental group was changed each hour into supine, semi-Fowler’s (up to 30°) and elevated (up to 45°) positions. A checklist was used for data collection. Results: None of the patients developed bleeding, hematoma or arterial thrombosis; therefore, no significant difference was found between the groups. Conclusion: change Position in bed may reduce back pain and promote physical comfort without increasing vascular complications. Keywords: Coronary angiography, change Position, Vascular complications.